Reduction Kinetics and Mass Transport of ZnO Single Entities on a Hg Ultramicroelectrode. Issue 10 (30th March 2020) - Karunathilake, Nelum; Gutierrez‐Portocarrero, Salvador; Subedi, Pradeep; Alpuche‐Aviles, Mario A.
Abstract: We discuss the electrolysis mechanism of colloidal ZnO NPs (10 nm diam.) in CH3 CN. Stripping the preconcentrated Zn(Hg) allows quantification of the ZnO electrolyzed during stochastic interactions with the Hg surface. We model the mass transport taking the charged agglomerates of ZnO NPs as ionic species to calculate their migration and diffusional contributions. In unsupported suspensions, the mobility and positive zeta potential enhance transport towards the Hg UME. The NP electrolysis generates ionic species, increasing the migration rate and allowing lower detection limits compared to weakly supported suspensions, where the electrolyte modifies agglomerate charge and colloidal properties. We determine the kinetic constant ( k f, in cm/s) for the ZnO reduction from the electrolysis transient model for destructive collisions of single entities, corrected for the potentiostat time constant. While most reduction events happen within 100 ms, the single entity model is consistent with mass transport studies over longer experimental times (1800 s). Abstract : A transport model : Colloidal ZnO NPs (10 nm diam.) are electrolyzed in CH3 CN to make Zn(Hg). The stripping peak is proportional to the concentration of unsupported particles. The kinetic constant for the ZnO reduction is determined from the electrolysis transient model which is corrected for the delay induced by the potentiostat. Most reduction events happening within 100 ms, but consistent with mass transport studies more extended over experimental times.